How does product packaging features influence the purchase decision of young adult? - Mollika Roy; Barun Kummer Bhattacharja; Iffat Jahan (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2023)
Packaging is more than just a suitable way of showcasing a product or getting a product to the consumer without reaching any damage. Here, we intended to know the relative significance of different features of packaging in purchase decision-making. We controlled the diversity of products and their confounding effect in the decision-making task by giving participants a particular product category (toiletries items) in the instruction. A survey was conducted on 386 Bangladeshi adult participants to rate their attitudes toward 11 different packing features when they make a purchase decision. The finding shows that participants rated printed detail on the package as the most important attribute which can manipulate their purchase choice. Moreover, they rated Convenience packaging, Hygienic wrapping material, convincing words on the packet, and attractiveness as the top five packaging features for young Bangladeshi adults, respectively. We found some significant gender differences in four features of product packaging. Bangladeshi adult females are more influenced by the attractiveness, colourful packet, convenience packaging, and convincing words on the packet than male customers. This finding could be an important addition to consumer behaviour literature. Moreover, marketers and designers would know their customer's needs and will be able to use this knowledge in product packaging as a reliable source of marketing strategy to increase their product sales.Keywords: product packaging; consumer behaviour; decision making; young adults